Encyclopaedia of women health and empowerment - 11 Health development and gender eqality Healthcare system, gender bias and legal rights - Kumar, Meenal; Ganguly, N. K.; Kumar, R. (New Delhi Deep & Deep Publications, 2009)
Health development and empowerment